Slope mass rating of rock slopes of the Malekhu River, central Nepal Lesser Himalaya - Tamrakar, Naresh Kazi; Singh, Jaya Laxmi (Journal of Nepal Geological Society, 2014)
The Malekhu River is one of the major tributaries of the Trishuli Ganga River fl owing from the south in Malekhu region, central Nepal. Riverbank slope stability is a topic of concern as rock mass condition and slope stability of riverbank slopes are important parameters for riverbank erodibility. Fourteen sites in the Malekhu River were selected for rock mass rating (RMR) and then slope mass rating (SMR) by using a graphic method. The potentially vulnerable sites were identifi ed after conducting field study in different slopes. The results indicate that there occur modes of failures ranging from stable (good rock mass) to partially stable (normal rock mass) in all the study sites. The unstable (bad rock mass) and completely unstable (very bad rock mass) slopes are, however, distributed only in some slopes. The unstable slope of plane failure mode is Ka1, whereas the completely unstable slopes of plane failure mode are Rb2, Ml1 Slope 1 and Ml2. The unstable slope of toppling failure mode is Ml2. When wedge failure mode is considered, the slopes at Ti1 and Ka1 are unstable while the slopes at Kh1, Ka1, Ml1 Slope 1 are completely unstable. The rock slopes with unstable to completely unstable states are considered bad (SMR Class IV: 21–40) to very bad (SMR Class V: 0–20) rock mass with fair to poor rock mass rating, respectively. These bad to very bad rock mass slopes are vulnerable to slope movements and river erosion, and they require mitigative measures.